2020
DOI: 10.3389/fimmu.2019.03041
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Carotenoids in Invertebrate Immunology

Abstract: Carotenoids are biologically active pigments that are well-known to enhance the defense and immunity of the vertebrate system. However, in invertebrates, the role of carotenoids in immunity is not clear. Therefore, this study aims to review the scientific evidence for the role of carotenoids in invertebrate immunization. From the analysis of published literatures and recent studies from our laboratory, it is obvious that carotenoids are involved in invertebrate immunity in two ways. On the one hand, carotenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 128 publications
1
44
0
Order By: Relevance
“…Carotenoids are universal stimulators of immunity; metabolic cleavage of β-carotene generates retinaldehyde molecules that activate the RXR receptor ( 140 ), with resultant regulation of many immune-related genes across species. Experiments with invertebrates showed that carotenoids regulate the expression of immune-related genes such as TLRs, heat shock proteins HSP70 and HSP90, thioredoxin-like protein (TRX), and peptidoglycan recognition receptor proteins (PGRPs) ( 22 ), possibly having a positive impact on the innate immune response against pathogens. Experiments with rabbits showed that carotenoids can enhance the humoral immune response by increasing serum IgM, IgG and IgA levels ( 23 ).…”
Section: The Role Of Micronutrients In Immune System Function In Vitro and In Vivomentioning
confidence: 99%
“…Carotenoids are universal stimulators of immunity; metabolic cleavage of β-carotene generates retinaldehyde molecules that activate the RXR receptor ( 140 ), with resultant regulation of many immune-related genes across species. Experiments with invertebrates showed that carotenoids regulate the expression of immune-related genes such as TLRs, heat shock proteins HSP70 and HSP90, thioredoxin-like protein (TRX), and peptidoglycan recognition receptor proteins (PGRPs) ( 22 ), possibly having a positive impact on the innate immune response against pathogens. Experiments with rabbits showed that carotenoids can enhance the humoral immune response by increasing serum IgM, IgG and IgA levels ( 23 ).…”
Section: The Role Of Micronutrients In Immune System Function In Vitro and In Vivomentioning
confidence: 99%
“…Additionally, the administration of carotenoids, such as ASX and lycopene, have been observed to enhance the production of antioxidative enzymes, such as SOD and GPX, and the cellular endogenous antioxidants, such as GSH, in fish, mammals, and invertebrate [ 27 , 37 , 43 , 74 , 107 , 142 , 143 , 146 , 147 ]. The supplementation of carotenoids has also been found to upregulate the expression of HSP in the tissue of several animal species and cultured cells [ 27 , 107 , 146 , 148 , 149 ]. Taken together, these results suggest that dietary carotenoids can improve the antioxidative defense including antioxidative enzymes, cellular endogenous antioxidants, and HSP, and strengthen the ability of resistance against oxidative stress in the body.…”
Section: Activities Of Carotenoids In Farmed Fishmentioning
confidence: 99%
“…The high carotenoid content is believed to promote environmental toleration and disease resistant in Nan'ao Golden Scallop (Tan et al . 2020d,e,f).…”
Section: Bivalve Selection Breeding Programmes and Its Implication Ofmentioning
confidence: 99%